Chromosomes and Mitotic Cell Division Phase In Onion Roots After 24 Hours Acetoorcein Soaking Time - Kusumaningrum, Hermin Pancasakti; Lunggani, Arina Tri; Nurhakim, Muhammad Amal (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2012)
Onions (Allium cepa) are usually used in vitro to assess effect of chemical subtances by allowing developing roots to come into contact with substances to be tested. Acetic orcein staining of onion chromosomes has remained a standard method of preparation. However, aceto-orcein stain is corrosive and poisonous chemical substances since it containing oxidising agents such as organic peroxides, the toxic substances which are are cyanides, acid corrosives agents, and also radioactive substances. This research study mitotic activity in the roots of onion plants to determine the effects of soaking time of aceto orcein dye on actively dividing root cells. A series of several root tip from each bulb was harvested were soaked in 1, 3 and 24 hours on aceto-orcein stain and processed further for cytological studies by the aceto-orcein squash technique. The research was carried out to study the effect of to mitotic index and chromosomal aberration on onion root. It will determine the percentage of cells that are undergoing mitosis. The squash techniques were used to observe mitosis in the tip of onion root cells during actively mitotic division cells time. Mitotic divisions occur in several phases, consist of prophase, metaphase, anaphase, telophase and interphase. Experiment were repeated six times for every soaking time. The data was analyzed by using T-Test. The result showed that various duration of soaking time significantly influenced the reduction of mitotic index value. The lowest mitotic index on glyphosate concentration 100 ppm i.e. 10. 73% and 7.19% for the duration of soaking time 3 and 6 hours. The highest mitotic index on glyphosate concentration 0 ppm i.e. 37.71% and 32.76% for the duration of soaking time 3 and 6 hours. The result also showed that the chromosomal aberration were increased significantly. The lowest chromosomal aberration obtained i.e. 2.55% and 2.96% for the duration of aceto orcein soaking time 1, 3 and 24 hours. The highest chromosomal aberration obtained i.e. 21.71% and 36.26% for the duration of soaking time 1,3 and 24 hours. The type of chromosomal aberration were abnormal prophase, stickiness, bridge, abnormal anaphase, clumping chromosome, c- metaphase, change of nucleous shape and size. At 72h, their cytotoxic effects on the root tips showed strong growth retardation in high concentrations of all the wastewaters. Compared to the control, treatment with the wastewaters resulted in root growth inhibition with EC50 values of 35, 50 and 62% for bottling, rubber and brewery effluents respectively, and decrease in mitotic index with increasing concentration for all samples and these were statistically significant (p<0.05). Chromosomal aberrations induced in the onion root tip cells were mostly sticky chromosomes and bridges. Chromosomes with disturbed spindles and fragments were also present in appreciable amounts. Based on the EC50 values, the bottling wastewater was most toxic, followed by rubber effluent while effluents from the brewery were least toxic. The findings in this study indicate that there are toxic chemicals present in the wastewaters which are responsible for the observed genotoxic effects on the onion root tip cells. The study also reveals that the Allium test is a useful and reliable tool for the genotoxicity screening of industrial effluents which could be employed by environmental managers before these effluents are finally discharged into the environment. Key words: chromosomes, onion roots, acetoorcein